Antipodean Prints: Joseph Burke and the development of the University of Melbourne's Print Collection. Issue 2 (2nd April 2020) - Lo Conte, Angelo
ABSTRACT: The Baillieu Library of the University of Melbourne hosts one of the finest old masters' print collections in Australia, the equivalent of a state institution or national gallery. Begun with a donation made in 1959 by Dr Orde Poynton, it was enriched in the early sixties thanks to bequests and acquisitions orchestrated by Joseph Burke, Melbourne's first Herald Chair of Fine Arts, and enhanced by the participation of key figures in the Australian art world. Prompted by new archival discoveries, this paper retraces how the print collection was created, highlighting the acquisitions made in the period 1960–1966. The paper highlights the collection's teaching function and emphasises how its development was supported by an extraordinary synergy between art historians and local philanthropists.